2011
DOI: 10.1039/c0cc05039c
|View full text |Cite
|
Sign up to set email alerts
|

First one-pot stereoselective synthesis of cis-2,3-dihydro-4-perfluoroalkyl-1H-1,5-benzodiazepines via a catalyst-free three-component reaction

Abstract: cis-2,3-Dihydro-4-perfluoroalkyl-1H-1,5-benzodiazepines were stereoselectively synthesized using a one-pot, catalyst-free, three-component reaction. This novel, efficient and convenient approach was used to synthesize 22 related products in moderate to excellent yields, demonstrating the scope and potential economic impact of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 38 publications
(2 reference statements)
0
9
0
2
Order By: Relevance
“…The electronic effect of substituents efficiently alters the yield of the ectron-withdesired product. Electron-releasing groups on aldehydes provide much better results than electronwithdrawing groups [263].…”
Section: Synthesis Of Diazepinesmentioning
confidence: 99%
“…The electronic effect of substituents efficiently alters the yield of the ectron-withdesired product. Electron-releasing groups on aldehydes provide much better results than electronwithdrawing groups [263].…”
Section: Synthesis Of Diazepinesmentioning
confidence: 99%
“…Thus, we developed a first stereoselective synthesis of perfluoroalkylated 1,5-benzodiazepines 85 via a one-pot, catalyst-free, three-component reaction, using methyl perfluoroalk-2-ynoates 1 as the key building blocks (Scheme 26). [44] Both aromatic and aliphatic aldehydes 83 reacted readily with o-phenylenediamine 84 and methyl perfluoroalk-2-ynoates 1 to afford the corresponding 85. The experimental results also indicated that this reaction was The high stereoselectivity shown in this cascade reaction could be explained by the pathway in Scheme 27.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…在以往文献报道 [3,8,9] 和我们自己工作的基础上, 推 断反应机理如 Scheme 1. [8] 138.3, 136.8, 134.9, 134.6, 133.4, 133.1, 131.6, 130.6, 130.5, 129.4, 128.5, 123.4, 120.3 (q, 1 J C -F =275 Hz), 38. 4,135.7,134.4,129.8,129.1,123.55,119.6 (m,CF 3 [11] …”
Section: 结果与讨论unclassified
“…然而目前有关氟代烷基直 接取代在杂环部位的 1,5-苯并二氮-2-酮类化合物的 合成的报道却很少, 主要是采用氟砌块策略, 用三氟乙 酰乙酸乙酯与邻苯二胺在近 150 ℃条件下缩合得到三 氟甲基取代的 1,5-苯并二氮-2-酮 [7] . 2011 年, 本课题 组报道了以含氟炔酸甲酯为含氟砌块, 与邻苯二胺和芳 醛一锅法合成了一系列多氟烷基取代的 1,5-苯并二氮 衍生物 [8] . 这里, 本文在前面工作的基础上, 在没有催 化剂存在条件下, 使含氟炔酸甲酯与邻芳基二胺在无水 甲苯中 80 ℃反应 24 h, 即得到 4-多氟烷基-1,5-苯并二 氮-2-酮类化合物.…”
unclassified